Prerequisites and limitations of the use of oral anticoagulants in pregnant women in real-world clinical practice - Kh. A. Zagorodnikova; O. A. Bettikher; I. Ye. Zazerskaya (Реальная клиническая практика: данные и доказательства)
Relevance. Anticoagulants are commonly used during pregnancy is a fairly common practice. Due to the widespread use of oral anticoagulants in real practice and the high frequency of unplanned pregnancy, physicians should assess the risks and plan pregnancy management strategies.Objective. The purpose of this analysis was to assess the legal background and evidence on the risks associated with the use of oral anticoagulants in pregnant women in real-world clinical practice.Materials and methods. An analysis of the official instructions for the use of oral anticoagulants registered in Russia, an analysis of the published literature on reproductive toxicity and the use of drugs during pregnancy, and a general comparative analysis of the predominance of individual oral anticoagulants in practical healthcare in Russia.Results. The results of the analysis revealed high variability in the restrictions on the use of oral anticoagulants during pregnancy. At the same time, the actual evidence of reproductive toxicity for drugs does not differ significantly and indicates the absence of signals of potential teratogenicity, at least based on the available number of observations. The maximum number of pregnancy observations exceeding the number of observations on warfarin use was reported for the use of rivaroxaban (505 cases in the largest analysis). The remaining representatives are described by several dozen observations. In Russia, the use of oral anticoagulants is also a prerequisite for the more likely use of rivaroxaban and apixaban in cases of unplanned pregnancy.Conclusions. In real-world clinical practice, exposure to oral anticoagulants is a prerequisite for pregnancy, which requires decision-making on strategies for pregnancy management. Instructions for the use of drugs do not contain reasonable information or formulations for decision-making based on accumulated knowledge about reproductive toxicity. Based on published data on the use of drugs in this group during pregnancy in real-world clinical practice, there is no sign of teratogenic potential for all representatives, with the exception of warfarin, whereas the largest number of observations concerns the most commonly used rivaroxaban.